2019
DOI: 10.4103/ajns.ajns_294_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 1 g and 2 g of intrawound vancomycin powder application for prophylaxis in posterior instrumented thoracic or lumbosacral spine surgery: A preliminary report

Abstract: Background: Surgical site infection (SSI) after instrumented spinal surgery is one of the most serious complications in spite of the routine use of prophylactic intravenous (IV) antibiotics. Many studies have suggested that intrawound vancomycin powder, applied during the intraoperative period, may decrease the incidence of SSI after surgery. However, the appropriate dose of vancomycin has not yet been reported. Purpose: The purpose of the study is to compare between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…A total of 2367 relevant studies were screened, of which 42 studies between 2011 and 2022, met the inclusion criteria and were involved in the meta‐analysis. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Data obtained from these studies were shown in Table 2 . The selected studies included 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2367 relevant studies were screened, of which 42 studies between 2011 and 2022, met the inclusion criteria and were involved in the meta‐analysis. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Data obtained from these studies were shown in Table 2 . The selected studies included 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control.…”
Section: Resultsmentioning
confidence: 99%
“…The current meta‐analysis involved 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The powdered vancomycin had significantly lower surgical site wound infections after spinal surgery, deep surgical site wound infections after spinal surgery, superficial surgical site wound infections after spinal surgery, and surgical site wound infections after cranial surgery compared to control in subjects with neurosurgery. The analysis of outcomes should be done with caution even though the low number of studies with a low sample size, 3 out of the 42 studies, in the meta‐analysis, and a low number of studies in certain comparisons.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Intrawound vancomycin used in spine surgery significantly decreases risk of postoperative infection. 36 This finding likely inspired local vancomycin use in primary hip and knee arthroplasty. 37 Indeed, a previous systematic review and meta-analysis demonstrated that intrawound vancomycin may decrease the risk of PJI in primary (OR 0.44, 95% CI 0.24 to 0.77) and revision (OR 0.28, 95% CI 0.13 to 0.61) TKA and THA; however, that study did not evaluate its safety.…”
Section: Discussionmentioning
confidence: 99%
“…Estos hallazgos son comparables con otras cohortes que han establecido a la vancomicina en la herida como eficaz para prevenir la ISQ. [6][7][8][9][10][11][12][13][14][15] En 2011 Sweet y colaboradores realizaron un estudio retrospectivo para evaluar la seguridad y eficacia de la aplicación local de VP como complemento para la profilaxis de ISQ de la columna torácica y lumbar instrumentadas por Paciente con infección profunda del sitio de herida quirúrgica, perteneciente al grupo sin uso de vancomicina tópica; posterior a la complicación, se empleó el sistema de presión negativa para lograr el cierre completo de la herida.…”
Section: Discussionunclassified
“…[1][2][3][4][5] El bajo costo, la disponibilidad y fácil aplicación de la vancomicina en los centros de referencia nacional para cirugía de columna brinda la oportunidad de ofrecer una alternativa eficaz y segura en la prevención contra agentes infecciosos, S. epidermidis y S. aureus, que resultan sensibles a la acción de la vancomicina en polvo (VP). [6][7][8][9][10][11][12][13][14][15] Cohortes en Norteamérica describen el costo de la VP en 12 dólares y revelan costos por atención individual a un paciente por cirugía de columna en alrededor de 92,884 dólares, se determinó que la infección incrementa el costo en un rango de 14,459 a 114,763 dólares. A nivel mundial se estima que los costos para tratar una infección de sitio quirúrgico (ISQ) va desde el tratamiento antimicrobiano oral para un caso superficial alrededor de los 400 dólares hasta cifras mayores a los 30,000 dólares que toman en cuenta la hospitalización y cirugías de revisión en infecciones profundas.…”
Section: Wwwmedigraphicorgmx Introducciónunclassified